Obravnavanje omejitev v večkriterijski optimizaciji - Erzin, Eva (Matrika, 2019)
Article deals with constrained multiobjective optimization problems. A good approach to solving them is using genetic algorithms that this article first describes in general terms and then explains two of them, NSGA-II and MOEAD more thoroughly. Some constraint handling methods that allow for the existing multiobjective algorithms to be adapted for constrained multiobjective optimization are presented. Finally, two multiobjective constrained test problems are presented along with the results of testing the aforementioned genetic algorithms and constraint handling techniques on them.
Keywords: constrained multiobjective optimization; genetic algorithms; genetski algoritmi; MOEA/D; NSGA-II; večkriterijska optimizacija z omejitvami